Litigating Abortion Access Cases in the Post-Windsor World - Anderson, Bebe J. (Columbia Journal of Gender and Law, 2015)
Exploring how to apply lessons learned from the successful challenge to the federal Defense of Marriage Act (DOMA), not only to ongoing marriage equality work but also reproductive rights work, is a productive and important endeavor, given the similarities between the two. An overarching similarity is that the two movements are grounded in many of the same core values: valuing human dignity, personal decision-making, and fairness. As the plurality opinion by Justices O’Connor, Kennedy, and Souter in Planned Parenthood of Southeastern Pennsylvania v. Casey states: Our cases recognize “the right of the individual, married or single, to be free from unwarranted governmental intrusion into matters so fundamen- tally affecting a person as the decision whether to bear or beget a child.” Our precedents “have respected the private realm of family life which the state cannot enter.” These matters, involving the most intimate and per- sonal choices a person may make in a lifetime, choices central to personal dignity and autonomy, are central to the liberty protected by the Four- teenth Amendment. At the heart of liberty is the right to define one’s own concept of existence, of meaning, of the universe, and of the mystery of human life. Beliefs about these matters could not define the attributes of personhood were they formed under compulsion of the State.